Boosting confidence in Indonesian women: Unraveling Instagram’s CrossFit influence and social comparisons - Zein, Duddy; Setiaman, Agus (Faculty of Communication Sciences Universitas Padjadjaran, 2023)
The emergence and popularity of CrossFit in Indonesia have challenged conventional fitness norms and gender expectations, potentially contributing to heightened confidence levels among Indonesian women. The advent of social media platforms like Instagram has further amplified these shifts. This research aims to investigate how women CrossFit exercisers in Indonesia engage in social comparisons on Instagram, specifically examining the role of this social media platform within the CrossFit context. By addressing a notable research gap in the literature, this study employs a comprehensive survey incorporating seven distinct scales and 50 carefully crafted questions. These measures aim to assess social comparison behavior, self-confidence, feelings of superiority, and patterns of Instagram usage among women involved in CrossFit activities in Indonesia. Correlation analysis is utilized as a statistical tool to test the research hypotheses. The findings of this study reveal multiple highly significant outcomes, providing a comprehensive understanding of the Indonesian CrossFit community. These findings shed light on important facets such as women CrossFit exercisers’ engagement with Instagram, the prevalence of social comparison tendencies, and levels of self-confidence within this population. However, further investigation is necessary to gain deeper insights into the intricate interplay between social comparison, Instagram usage patterns, and the experiences of women participating in CrossFit activities, particularly within the Indonesian context.